Characterisation And Pathogenicity Studies Of Malaysian Isolates Of Avian Pox Virus - Sivasothy, Arumugam (1997)

(untitled)
Avian pox is one of the important viral diseases in avian species of which, fowl pox is the most common disease and is usually controlled by vaccination. However, in recent years, outbreaks of the disease in vaccinated flocks have been reported. Therefore, it is important to study the local isolates as well as vaccine strains in order to determine the cause of the outbreaks. This study was conducted to isolate, identify and characterise the field strains of avipox virus, which caused outbreaks among poultry in Malaysia. The isolates were also compared with the vaccine strain (TC-B I2) by pathogenicity studies in chickens. Initial characterisation of isolates involved morphology by electron microscopy, changes in embryonated chicken eggs, inclusion body formation, immunoperoxidase test and cytopathogenicity in cell culture.Five avipox viruses were isolated from chicken, pigeon and turkey. Negative contrast electron microscopy showed the unique morphology of the isolates and did not show an y differentiation among the isolates in respect to their origin. The isolates were titrated in embryonated eggs and the isolates from pigeon and turkey gave lower titre in comparison to other isolates. On chorioallantoic membrane (CAM), mother pock lesions were produced by the isolates from pigeon and turkey in comparison to the isolates from chicken which produced scattered pock lesions.